Arm-wrestling injuries – A systematic review of the medical literature - Correia, Renan Felipe; Ribeiro, Alex Natalino; Araújo, Roberto Pires de (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Arm wrestling is a popular sport due to its simplistic nature and great appeal in popular culture. Unfortunately, it can lead to serious fractures. An understanding of these injuries and its mechanisms is vital to the undertaking of safe practice methods for this sporting modality. Objectives: This study aimed to review articles that demonstrate case reports about arm-wrestling related fractures. Methods: PubMed’s database was searched with the keywords “Arm Wrestling,” Arm-wrestling,” and “Armwrestling.” Ofthe 34 articles found, 11 were fit to compose this review, being grouped into studies that dealt with adults and studies that dealt with adolescents. Results: Of the 63 adult subjects reported, 62 suffered fractures of the distal third of the humerus, occasionally accompanied by butterfly fractures and radial nerve palsy. Of the 22 adolescent subjects reported, 20 suffered fractures of the humerus medial epicondyle, never accompanied by butterfly fractures, and sometimes accompanied by ulnar nerve palsy. All injuries stemmed from unbalanced torsional forces suffered by the humerus from its own musculature. Conclusions: The injury profile presented by both populations is very homogeneous between the two different groups, which leads us to believe that correct technique can be a great ally in arm wrestling injury prevention. Athletes, as well as common practitioners, should be coached as to avoid these unfavorable positions and techniques